The Effect of Corrective Discipline and Intrinsic Motivation on Employee Performance at PDAM Tirta Darma Ayu Indramayu - Syifa Rahma Aliyah; Lisa Harry Sulistiyowati; Sandi Nasrudin Wibowo (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the effect of corrective discipline and intrinsic motivation on employee performance at PDAM Tirta Darma Ayu, Indramayu Regency. A quantitative causal associative design was employed using primary data collected through questionnaires distributed to 107 employees selected through a saturated sampling technique. Data were analyzed using SPSS through validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination. The results show that corrective discipline and intrinsic motivation have positive and significant effects on employee performance, both partially and simultaneously. The model explains 44.8% of employee performance variance. These findings suggest that fair corrective discipline and stronger intrinsic motivation can improve employee performance.